Analisis Kualitas Pelayanan Administrasi Kependudukan pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tapanuli Selatan - Dudi Komarudi; Isnaini Isnaini; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to describe the quality of population administration services at the Department of Population and Civil Registration of South Tapanuli Regency. This research is a descriptive study using a qualitative approach. Data collection techniques were carried out by observation, interview, and documentation techniques. The theory used in this study uses the Five Dimension of SERVQUAL theory according to Zeithaml, Parasuraman, and Berry. Population Administration Services At the Department of Population and Civil Registration there are constraints on Human Resources that are needed to be placed in indispensable parts, including the Population Database Admin still not meeting the educational criteria and training and education training is needed, the number of population administration service operators is still lacking in serving the community where one service operator officer processes document data from more than one sub-district. Geographical and demographic location of the South Tapanuli Regency Population and Civil Registration Office which is relatively far from the sub-district village whose residents live in the area. The innovation of ball pick-up administration services through the population service car that has been running still needs to be improved. Support for the Population Service's budgetary resources is still not optimal in order to meet the Excellent Service criteria. Improving the availability and quality of Population Data and Information Improving public services in the field of population and civil registration. encourage people's awareness of the importance and ownership of population documents.